Black Women Leading Education for Social Justice in the Region of Baixada Fluminense, Rio de Janeiro, Brazil - Malachias, Rosangela; Laudino, Laudilea Aparecida de Lourdes; Balbino, Teresa Cristina dos Santos (Frontiers in Education, 2020)
This paper explores the interface between the fields of Education and Communication with respect to developing narratives that can identify leadership among women who live daily with social inequalities and violence. These studies, debates, and research took place at the AFRODIÁSPORAS Research Center on Black Women, Audiovisual Culture, and Educommunication in Urban Peripheries at the Rio de Janeiro State University (UERJ) School of Education from Baixada Fluminense (FEBF), Duque de Caxias city, RJ, Brazil. Two studies were chosen as examples of the specific leadership developed by black women using concepts from Education, Communication, Intersectionality, and a daily struggle against prejudice and racism. The first study reports the experiences of a black deaf woman who teaches sign language alongside the history and culture of black deaf people. The second introduces a young black filmmaker who produces new portrayals of the Baixada Fluminense (BF) region. Findings: Both studies show the authorship of the interviewees, demonstrating that education and black consciousness empower people to become leaders who respond to social exclusion. Non-formal education has been employed as a method to propagate narratives refuting stereotypes and colonial beliefs that still appear on the curriculum of formal education and in hegemonic media. These two young black women are protagonists, educommunicators, social activists, and leaders.